Етапи моніторингу організації виховної роботи у вищому навчальному закладі - Дурманенко, Оксана Леонідівна; Durmanenko, Oksana L. (Сумський державний педагогічний університет ім. А. С. Макаренка., 2014)
У статті розкривається сутність поняття педагогічного моніторингу та моніторингу організації виховної роботи у вищому навчальному закладі. Характеризується поетапність моніторингу організації виховної роботи у вищому навчальному закладі як одна із особливостей його реалізації. Аналізуються три етапи моніторингу організації виховної роботи: підготовчий, практичний та аналітичний. Наголошується на цілісності моніторингу організації виховної роботи у вищому навчальному закладі, а відтак на взаємозалежності визначених етапів. The article describes the experimental aspects of the definition of monitoring level in the organization of educational work in higher educational institution. The author proposes a number of criteria on the basis of the structure in the organization of educational work in higher educational institution and monitoring requirements: motivational, cognitive, practical, effective, and corrective and respectively their indicators. The indicators of motivation criterion in research of a monitoring level in organization of educational work are defined: the awareness by the subjects of the educational work of the need to conduct such monitoring as a means of optimization of educational work (deep, situational, superficial, unconscious); motivation monitoring (clearly defined, situational, missing); motivation of professional activity (internal, active; internal; passive foreign missing). The indicators of cognitive criteria are: ownership of the monitoring concepts (deeply conscious, reproductive, superficial, partial or non partial); mastering the methods of monitoring research (creative, reproductive, situational, dogmatic or missing); monitoring of knowledge (profound, reproductive, fragmentary, elementary). The indicators of the practical criteria are the following: determination of the aim and objectives of monitoring (clear, situational, fragmentary, and superficial); implementing adequate specific purpose of monitoring methods (creative, reproductive, fragmentary and dogmatic; substantiation of conceptual and procedural aspects of the monitoring system, adequate, superficial, incomplete or missing); reporting (system-structured, structured superficial, primitive). The indicators of effective criteria are defined: the analysis of documents (plans, programs, reports, concepts) (statement of purpose, concreteness, executors, terms, principles, consistency, accounting of interests of the subjects of educational work; information on the execution of decisions, the content, forms and methods of organization of educational work)(system, sufficient surface, primitive); activity of subjects in educational work (participation in events, responsibility, initiative, creativity) (high, enough, low); the activities of students‘bodies self-government (creativity, activity, social orientation) (creative, episodic, passive); personal growth of students (social values, objective self-esteem, creativity, motivation of the professional activity, communicative and organizational skills, ability to self-regulation and self-actualization) (high, enough, medium, and low levels in accordance with diagnostics). Indicators of corrective criteria are: changes in the planning system-grounded, well-reasoned, superficial, and missing); the modification of the contents of educational work (creative, reproductive, fragmented, missing); recommendations on the use of methods and forms of educational work (justified, reasonable, superficial, and lacking); modelling of the updated structure of organization of educational work (system-grounded, well-reasoned, schematic is missing).
Criteria and indicators for determining the level of monitoring organization of educational work in higner educational institution
Keywords: моніторинг; педагогічний моніторинг; моніторинг організації виховної роботи; етапи моніторингу; організації виховної роботи; вищий навчальний заклад; monitoring; pedagogical monitoring; monitoring of the organization in educational work; the criterion; indicator of the criterion; the level of monitoring